English Language Learning Strategies used by Science Students - Syamaun, Nur Afni; Kasim, Usman; Muslem, Asnawi (Issues in Language Studies, 2019)
Learning strategies are ways employed by learners to enhance their learning. An active use of language learning strategies helps learners in control of their own learning by developing language skills, increasing confidence, and motivation in learning process. This study aims to investigate the dominant language learning strategies used by science students. It focused on listening, speaking, reading, and writing strategies that was studied using descriptive qualitative method. The subjects of this study were 56 eleventh-grade science students from the senior high boarding school of Darul Ikhsan. The questionnaire developed by Rubin and Thompson (1994) was distributed and the data was analyzed by looking at the highest frequency of students’ choice. The results indicated that the students employed cognitive strategies, metacognitive strategies, affective strategies, compensation strategies, and social strategies. However, the students used dominantly cognitive learning strategies across the four language skills. The findings recommended that students should be trained to use learning strategies properly. In addition, English teachers should consider the learners’ strategies by asking their intentions and use appropriate teaching methods.